Novel low-sodium salt formulations combined with Chinese modified DASH diet for reducing blood pressure in patients with hypertension and type 2 diabetes: a clinical trial - Zhang, Ziyan; Zhou, Xiaomeng; Mei, Ying; Bu, Xiaoqing; Tang, Jie; Gong, Tao; Liu, Guowei; Cai, Shuwen; Ren, Yanni; Mu, Lihong (Frontiers in Nutrition, 2023)
Abstract Background: In this study, we aimed to explore the antihypertensive effect of 23% and 52% concentrations of low-sodium salt combined with the Chinese Modified Dietary Approaches to Stop Hypertension (CM-DASH) diet in patients with hypertension and type 2 diabetes. Methods: We conducted a randomized controlled single-blind trial with a semi-open design. One hundred and thirty-two participants were randomly assigned into Group A (control group), Group B (52% low-sodium salt group), Group C (23% low-sodium salt group), and Group D (meal pack group) for 8 weeks of dietary intervention. All participants were followed weekly to collect data on blood pressure, salt use, and adverse events. Blood and 24-h urine samples were analyzed at baseline, 4 weeks, and the end of the intervention. Results: At the end of the intervention, the mean blood pressure decreased significantly by 10.81/5.03 mmHg, 14.32/6.32 mmHg, 14.20/6.59 mmHg, and 19.06/7.82 mmHg in Groups A–D, respectively, compared with baseline (P<0.001). Comparison between groups showed that the systolic blood pressure was lower in Groups C and D than in Groups A (-6.54 mmHg, -8.70 mmHg, P<0.05) and B (-6.60 mmHg, -8.76 mmHg, P<0.05), and the diastolic blood pressure was lower in Group D than in Group A (-5.17 mmHg, P=0.006). The 24-h urinary Na+ and Na+/K+ values were significantly decreased in participants using low-sodium salt (P<0.001). No serious adverse events occurred during the trial. Conclusion: Our preliminary results suggest that 23% and 52% concentrations of low-sodium salt combined with the CM-DASH diet can effectively reduce sodium intake and increase potassium intake in patients with hypertension and type 2 diabetes mellitus, thus achieving “salt reduction” and attaining standard, smooth, comprehensive management of patients with hypertension and type 2 diabetes.